SsAGM1-Mediated Uridine Diphosphate-N-Acetylglucosamine Synthesis Is Essential for Development, Stress Response, and Pathogenicity of Sclerotinia sclerotiorum - Zhang, Junting; Xiao, Kunqin; Li, Maoxiang; Hu, Hanlong; Zhang, Xianghui; Liu, Jinliang; Pan, Hongyu; Zhang, Yanhua (Frontiers in Microbiology, 2022)
The necrotrophic fungus Sclerotinia sclerotiorum is a devastating pathogen. S. sclerotiorum can cause Sclerotinia stem rot in more than 600 species of plants, which results in serious economic losses every year. Chitin is one of the most important polysaccharides in fungal cell walls. Chitin and β-Glucan form a scaffold that wraps around the cell and determines the vegetative growth and pathogenicity of pathogens. UDP-GlcNAc is a direct precursor of chitin synthesis. During the synthesis of UDP-GlcNAc, the conversion of GlcNAc-6P to GlcNAc-1P that is catalyzed by AGM1 (N-acetylglucosamine-phosphate mutase) is a key step. However, the significance and role of AGM1 in phytopathogenic fungus are unclear. We identified a cytoplasm-localized SsAGM1 in S. sclerotiorum, which is homologous to AGM1 of Saccharomyces cerevisiae. We utilized RNA interference (RNAi) and overexpression to characterize the function of SsAGM1 in S. sclerotiorum. After reducing the expression of SsAGM1, the contents of chitin and UDP-GlcNAc decreased significantly. Concomitantly, the gene-silenced transformants of SsAGM1 slowed vegetative growth and, importantly, lost the ability to produce sclerotia and an infection cushion; it also lost virulence, even on wounded leaves. In addition, SsAGM1 was also involved in the response to osmotic stress and inhibitors of cell wall synthesis. Our results revealed the function of SsAGM1 in the growth, development, stress response, and pathogenicity in S. sclerotiorum.